Protective effect of adenosine triphosphate and benidipine separately or together against cardiotoxicity caused by bevacizumab - Yildirim, Erkan; Yildirim, Nilgun; Cengiz, Mahir; Yazici, Gulce Naz; Coskun, Resit; Suleyman, Bahadir; Suleyman, Halis (Taylor & Francis Ltd, 2023)
Bevacizumab is a recombinant humanized monoclonal antibody whose adverse effects include cardiotoxicity. We investigated whether using adenosine triphosphate (ATP) or benidipine either separately or together protects against cardiac damage induced by bevacizumab in rats. Forty Wistar albino male rats were allocated to five groups of eight: bevacizumab (Bv), ATP + bevacizumab (ABv), benidipine + bevacizumab (BBv), ATP + benidipine + bevacizumab (ABBv) and untreated controls. Rats in the ABv group were injected intraperitoneally (i.p.) with 2 mg/kg ATP. The BBv group was given 4 mg/kg benidipine by oral gavage. The ABBv group was injected i.p. with 2 mg/kg ATP and simultaneously administered 4 mg/kg benidipine orally. One hour after administration of ATP, benidipine or normal saline, the Bv, ABv, BBv and ABBv groups were injected i.p. with 10 mg/kg bevacizumab. Malondialdehyde (MDA) and total glutathione (tGSH) levels were measured in cardiac tissue, and troponin I (TP I) and creatine kinase MB (CK-MB) levels were measured in blood samples. Tissue samples were examined for histopathology. We found the lowest TP I, CK-MB and MDA levels and the highest tGSH level in the ABBv group; these results were similar to the control group. Nuclei of cardiomyocytes in the BV group were misshapen and shrunken, and myofibers were disrupted; we also observed eosinophilic degeneration and interstitial edema. Blood capillaries were dilated and congested. We observed amelioration of these findings in the ABBv group. We found that ATP and benidipine alone or in combination reduced cardiac damage associated with the use of bevacizumab. ATP + benidipine combined therapy produced the most favorable results.
Keywords: Adenosine triphosphate; benidipine; bevacizumab; cardiotoxicity; heart; rats